Fatores influenciadores na decisão de produzir ou comprar: um estudo no sistema agroindustrial da cana - Consoli, Marcelo Henrique (2007)
Among the ways that companies can coordinate they activities and define the sources of resources, two are opposite: make or buy in market. In this way, companies choose one of these options or use hybrid coordination forms, that will define the level of vertical integration used by the company. The aim of this research is analyze and classify the main factors regarded by managers when deciding about the level of vertical integration to use in their strategies. Following this objective, it was made a review in the publications related to this subject, like strategy, decision making process, transaction cost economy, industrial organization and finance. The procedures to develop the research used case study methodology applied in the sugar cane sector, where three different sugar mills with distinct vertical integration levels were analyzed through secondary data and interviews. As results it shows a list of factors and situations to be analyzed and pondered to assist managers to organize their production systems and make most efficient decision making about make or buy